Pre- and post-race serum cardiac troponin T concentrations in Standardbred racehorses. (February 2020) - Hellings, I.R.; Krontveit, R.; Øverlie, M.; Kallmyr, A.; Holm, T.; Fintl, C.
Highlights: Serum cardiac troponin T (cTnT) concentrations in race-fit Standardbred horses was measured. These data could contribute towards establishing equine serum cTnT reference limits. The 97.5 percentile upper reference limit for cTnT was 27.4 ng/L (90% confidence interval 13.1–32.0). Post-race cTnT concentrations were significantly higher than pre-race concentrations. Females had higher post-race cTnT concentrations than males. Abstract: Elevated cardiac troponin T (cTnT) concentrations may provide evidence of myocardial injury but physiological post-exercise release also occurs. Reference intervals are not fully established in horses making interpretation difficult. The aims of this study were to establish an upper reference limit for serum cTnT, compare pre-and post-race serum cTnT concentrations, and to evaluate factors that may influence these in a population of healthy, race-fit Standardbred racehorses. Serum samples were collected pre- ( n = 108) and 1–2 h post-racing ( n = 101) and analysed using a high sensitivity-cTnT assay. Reference limits with 90% confidence intervals (CI) were calculated by non-parametric methods using the bootstrap method. Effects of sex, age, racing speed, distance, placings and track surface were assessed by fitting generalized linear models with an identity link function and inverse Gaussian distribution. The upper reference limit for serum cTnT concentration was 27.4 ng/L (90% CI 13.1–32.0). The median serum cTnT concentration was significantly higher 1–2 h post-racing compared to pre-racing ( P < 0.001). Age and sex did not significantly affect serum cTnT concentrations pre-racing ( P = 0.5 and P = 0.11). Cardiac troponin T concentrations were significantly higher post-racing in females ( P = 0.018). Racing speed and placings had no effect on serum cTnT concentrations post-race ( P = 0.71 and P = 0.66). The study contributed towards establishing an upper reference limit for serum cTnT concentrations in a population of race-fit Standardbreds and evaluated factors that may have influenced the results obtained.